Western Union Telegram from Senator Eugene McCarthy to Jane Tolmach - Eugene McCarthy:::::: (1968)
A Western Union telegram from Washington, D.C. that congratulates Jane Tolmach on being named to the California delegation to the Democratic National Convention. The sender states he plans to attend the delegation's meeting in Sacramento and looks forward to discussing new directions the nation and party must take in response to the people. The message is signed by Senator Eugene McCarthy of the United States Senate.